Predictive power of different obesity measures for the presence of diastolic dysfunction - Yalın Tolga Yaylalı; Güzin Fidan-yaylalı; Beray Can; Hande Şenol; Mehmet Kılınç; Mustafa Yurtdaş (KARE Publishing, 2018)
Objective: Body mass index (BMI) and waist circumference (WC) as measures of obesity have some limitations. The aim of this study was to evaluate whether one measure could predict the presence of diastolic dysfunction (DD) more accurately than the other measures. Methods: A total of 91 obese patients without any other risk factors for DD were prospectively enrolled. Echocardiographic examination was performed. DD was defined and categorized according to recent guidelines. The study participants were divided into 2 groups according to the presence of DD. Weight, height, and WC were measured; BMI and waist-to-hip ratio (WHR) were calculated; and a body shape index (ABSI) was calculated as WC/(BMI2/3height1/2). The associations between ABSI, BMI, WHR, and WC and the presence of DD were examined using logistic regression analyses. Analysis of covariance was used to examine the differences. Results: WC and BMI were significantly greater in subjects with DD (p=0.049 and 0.051, respectively). A greater BMI, WC, and WHR increased the risk of the presence of DD (BMIDD: odds ratio [OR]=1.096, p=0.024; WC-DD: OR=1.059, p=0.007; WHR-DD: OR=2.363, p=0.007). After adjustment for age and sex, only BMI continued to be significantly associated with DD (p=0.031). ABSI was not associated with DD. Conclusion: After adjustment for age and sex, BMI was the only predictor of DD in obesity. Despite its limitations, BMI may still be a potentially more accurate measure of DD compared with other obesity measures.